Biological markers for targeted action timing and phasing in archery - Trembach, A. B.; Shestakov, O. I.; Ponomareva, T. V.; Minikhanova, E. R. (Theory and Practice of Physical Culture, 2018)
Archery may be classified with the sport disciplines driven by targeted skillful actions. Movement accuracy is secured by a harmonized sequence of actions with the shooting process phasing and timing being critical for success. Objective of the study was to time, phase and analyze the bow shooting process using the relevant process biomechanical, electromyographic (EMG), electroencephalographic (EEG) and vegetative NS activity indices. Four Russian Masters of Sport were sampled for the standard shooting sequence profiling tests to obtain the following test data: kinematic parameters of the radiocarpal joint movements fixed at discretional frequencies of 50HZ and 120Hz; EMG of 8 core muscles; EEG in 19 points; electro-oculograms; pneumograms; ECG with application of the motor activity sensor; and with WinEEG software applied to process and analyze the EEG data. The movement profiling by the biological markers made it possible to identify the key periods of the shooting process i.e. the setup, preparation and execution periods with their phases. Setup Period I was classified into two phases designed to reach the optimal prime vertical posture. Dynamic postural control Period II includes three phases. And aiming Period III includes two phases followed by a shot. The biological markers to profile the radiocarpal joint travel trajectories versus the EEG data made it possible to analyze the athletes` functionality rates in Periods I and III and find logics in their variations versus the shooting accuracy rates.